2019
DOI: 10.1530/joe-18-0540
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circular RNAs in the immature and mature rat anterior pituitary

Abstract: Circular RNAs (circRNAs) are a new class of RNA that have a stable structure characterized by covalently closed circular molecules and are involved in invasive pituitary adenomas and recurrent clinically nonfunctioning pituitary adenomas. However, information on circRNAs in the normal pituitary, especially in rats, is limited. In this study, we identified 4123 circRNAs in the immature (D15) and mature (D120) rat anterior pituitary using the Illumina platform, and 32 differentially expressed circRNAs were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…However, circAkap17b levels in the anterior pituitary were shown to drop quite dramatically during the first 2 weeks after birth ( 104 ), such that its function in regulating FSH might be limited. Additional circRNAs were found differentially expressed in pituitaries from immature and mature rats (see below) and were predicted to interact with various miRNAs reported to regulate Fshb ( 105 ), although their function has yet to be demonstrated.…”
Section: Regulation Of Key Gonadotrope Genes By Enhancers Ernas and Regulatory Lncrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…However, circAkap17b levels in the anterior pituitary were shown to drop quite dramatically during the first 2 weeks after birth ( 104 ), such that its function in regulating FSH might be limited. Additional circRNAs were found differentially expressed in pituitaries from immature and mature rats (see below) and were predicted to interact with various miRNAs reported to regulate Fshb ( 105 ), although their function has yet to be demonstrated.…”
Section: Regulation Of Key Gonadotrope Genes By Enhancers Ernas and Regulatory Lncrnasmentioning
confidence: 99%
“…Possible functions were inferred by searching for protein-coding genes within 100 kb of the lncRNAs, and 3 lncRNAs (MSTRG.80236.1, MSTRG.80236.2 and MSTRG.80236.3) that were predicted to interact with Fshb showed similarly increased expression ( 133 ). This group also screened for functional circRNAs, using a similar approach, and detected 32 DE circRNAs in the sexually immature and mature rat anterior pituitaries ( 105 ). They predicted interactions of some of the circRNAs and miRNAs, which lead to the discovery of several circRNAs with potential to regulate Fshb by acting as miRNA sponges as detailed in the previous section (“Fshb is Regulated in cis by a Distal Enhancer and Possibly in trans by miRNA-Sponging lncRNAs”) ( 104 , 105 ).…”
Section: Screening For Functional Pituitary Lncrnas Associated With Sexual Maturation and Reproductive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an increasing number of reports have indicated that circRNAs play key roles in a variety of biological processes. In 2019, Han et al identified circRNAs in the anterior pituitaries of mature and immature rats [ 33 ]. However, information on circRNAs in the rat pituitary, particularly after GnRH treatment, is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…miR-7, with a high degree of pituitary specificity (Amar et al 2012, plays a vital role in regulating diverse biological processes such as insulin signaling (Fernandez-de Frutos et al 2019), neuronal processes (Hu et al 2019), diet-induced obesity (Gao et al 2019), EMT, trophoblast invasion (Shih et al 2019), hormone secretion, and hypogonadism (Ahmed et al 2017, Zhang et al 2017a. In our previous study, we analyzed the expression profiles of circRNA between mature and homologous immature rat pituitary tissue samples (Han et al 2019). Based on nextgeneration sequencing with circRNA and bioinformatics, we constructded circRNA-miRNA-mRNA networks in the rat anterior pituitary.…”
Section: Introductionmentioning
confidence: 99%